Electro-Fenton and Electro-Fenton-like with in situ electrogeneration of H2O2 and catalyst applied to 4-chlorophenol mineralization. (20th March 2016) - Santana-Martínez, Germán; Roa-Morales, Gabriela; Martin del Campo, Eduardo; Romero, Rubí; Frontana-Uribe, Bernardo A.; Natividad, Reyna
Graphical abstract: Highlights: Undivided electrochemical cell allows to in situ generate H2 O2 and its dissociation catalyst. Copper regenerates faster than iron. 4-CP mineralization is more efficient when Cu is used as H2 O2 dissociation catalyst. Graphite electrodes allow to conduct EF and EFL with relative low energy consumption Abstract: The in situ generation of H2 O2 and its dissociation catalyst were conducted in an undivided electrochemical cell with two set of electrodes (graphite for the former and Fe or Cu for the latter) energized by two different power sources. This arrangement allowed to conduct Electro-Fenton and Electro-Fenton like processes with less addition of chemicals than the conventional chemical process. 4-Chlorophenol was elected as model molecule. The studied variables were catalyst type (iron or copper), current density, oxygen flowrate, number and length of current pulses. It was concluded that Cu is a better catalyst for H2 O2 dissociation. Within the studied conditions, a maximum of 70% removal of TOC was attained by the Electro-Fenton-Like process. At the same conditions, only a 45% of TOC removal was achieved by Electro-Fenton. It was also concluded that unlike Cu, Fe should be added only at the beginning of the process since its later addition is rather detrimental due mainly to an accelerated *OH consumption by excess of metallic ions.